Achieving Competency for Year 1 Doctors in Singapore: Comparing Night Float or Traditional Call - Mae Yue Tan; Zong Jie Koh; Shoban Krishna Kumar; Rui Min Foo; Rou An Tan; Nisha Suyien Chandran; Jeremy Bingyuan Lin; Malcolm Mahadevan; Eng Loon Tng (The Asia Pacific Scholar, 2024)
Introduction: The night float (NF) system has been instituted in some hospitals in Singapore to improve the working hours and wellbeing of junior doctors. There have been concerns of compromised learning and patient safety with NF. The objective of this study is to compare clinical competency outcomes, based on existing assessment framework, between post-graduate year 1 (PGY1) doctors working on NF versus traditional call (TC) systems. The secondary aim was to explore patient safety outcomes between these groups of PGY1s. Methods: Data on the formal assessments of PGY1s using the Entrustable Professional Activities (EPAs) and medical errors were prospectively collected between May 2021 and April 2022 from two hospitals that employed different on-call systems. Data was analysed descriptively. Categorical data was analysed using the Chi-square test or Fisher’s exact test where appropriate. Results: One hundred and ninety-three PGY1s consented to the study. There was no statistically significant difference in the clinical competency of PGY1s in both groups. The number of PGY1s who had ‘needs improvement’ scores in a detailed EPA was not significantly different (9.0% in the NF group versus vs 3.7% in the TC group (p = 0.14)). They nonetheless passed the overall core EPA and no PGY1 failed their postings. No serious reportable medical errors occurred in either group. Conclusion: PGY1s who worked on NF are equally competent compared to those who worked on TC based on the EPA assessment matrix. Patient safety is not compromised by PGY1s working on NF.